Impact of the incorporation of probiotic strains and fruit by-products in fermented synbiotic soy product and on the composition and metabolic activity of the gut microbiota in vitro - Vieira, Antonio Diogo Silva (2018)
The present study aimed to develop a fermented soy beverage containing fruit by-products and probiotics and to evaluate the impact of this product on the composition and metabolic activity of the human intestinal microbiota using an in vitro simulation model of the intestinal conditions (TIM-2). Therefore, the present study was divided into three stages. Stage I was based on obtaining, processing and physical-chemical, microbiological and functional characterization of fruit by-products (acerola, orange, mango, and passion fruit) and soybean (okara), as well as amaranth flour. Additionally, the ability to use these vegetable by-products and amaranth flour by probiotic and non-probiotic strains was evaluated. The results showed that the acerola byproduct presented the highest dietary fibre content (48.46 g/100 g) among the by-products tested, as well as amaranth flour. Orange and passion fruit by-products were the substrates that most promoted the growth of bacterial populations, including strains of Escherichia coli and Clostridium perfringens. On the other hand, the acerola by-product was the substrate that showed the highest selectivity for beneficial bacteria. Also, in this stage, ten probiotic strains (seven lactobacilli and three bifidobacteria) and three starter strains (Streptococcus thermophilus) were tested for their ability to deconjugate bile salts and for proteolytic activity against milk and soy proteins. The results showed that none of the tested strain showed proteolytic ability against milk and soybean proteins. In addition, the probiotic strains Lactobacillus acidophilus LA-5 and Bifidobacterium longum BB-46 deconjugated more types of bile acids tested, and the strains of S. thermophilus tested showed no ability to deconjugate bile salts. Next, the acerola by-product (ABP) and the probiotic strains LA-5 and BB-46 were selected to continue stage II of the study (development of a fermented soy beverage). For this purpose, a 23 factorial design was used, in a total of 8 trials with three replicates of each one, and the effects of the probiotic strains and the acerola by-product on the physical-chemical, microbiological, and sensory characteristics of these fermented soy beverages were evaluated. At the same time, probiotic viability and survival under in vitro gastrointestinal (GI) simulated conditions were evaluated in fermented soy beverage (FSB). The results showed that the presence of BB-46 and ABP affected the sensory acceptability of FSB negatively. ABP also led to significant differences in the texture profile of the FSB (P<0.05). Populations of probiotic strains ranged from 7.0 to 8.2 log CFU equivalent/mL during 28 days of refrigerated storage (4° C) of FBS, and the co-culture (LA-5+BB-46) and the ABP did not affect the viability of both microorganisms significantly (P> 0.05). However, ABP increased the survival of BB-46 under in vitro simulated GI conditions significantly. For stage III, a 22 experimental design was performed. To evaluate the impact of these FBS on the composition and metabolic activity of the intestinal microbiota of lean and obese humans, a validated in vitro model called TIM-2 was used, available at the Maastricht University (Venlo, The Netherlands), which simulates normal conditions of the lumen of the proximal colon, with all parameters controlled by a computer. Samples were collected from TIM-2 to quantify probiotic microorganisms (LA-5 and BB-46), Lactobacillus spp., Bifidobacterium spp., and total bacteria, using the quantitative PCR method (qPCR) and the intestinal microbiota profile was determined using an Illumina Mysec Next Generation Sequencing (NGS) method. Concentrations of shortchain fatty acids and branched-chain fatty acids and lactate produced by the different microbiotas during fermentation in TIM-2 were also determined. The results showed that the lean microbiota presented the high production of acetate and lactate than the microbiota of obese individuals. Significant reductions in Bifidobacterium populations in the lean microbiota were observed at 0 and 48 h of an assay for all experimental meals, except for the meal that had the probiotic combination (LA-5 and BB-46) and the ABP supplementation, which showed an increased total Bifidobacterium and Lactobacillus populations throughout the experimental period for both microbiotas tested. The FSB supplemented with ABP presented the best characteristics regarding the modulation of the obese microbiota, with an increase in Bifidobacterium spp. and Lactobacillus spp. Additionally, after 48 hours of intervention in TIM-2, the obese microbiota was apparently similar to the lean microbiota, showing a beneficial modulation of this microbiota. The results suggest that the fermented soy beverage supplemented with the acerola by-product and the probiotic strains may present beneficial health effects. However, clinical studies are required to complement and confirm the results observed in the in vitro assays.